Pengembangan Sumber Daya Manusia - Suwarno, Djoko (Responsibilitas, 2010)
Abstract Human resource development program conducted in organization because the organization is a social system that canât be separated from its environment. Thus the organization and the environment have a mutual dependence and influenced one another. The process of human resource development should be based on what and who is going to be developed, how the end result and how its methods. Therefore, in doing development must consider environmental, organizational, and human characteristics, and management concepts. Keywords: sumber daya manusia, pengembangan.